2009
DOI: 10.1007/s00345-009-0466-1
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcomes and resource use of patients with neurogenic detrusor overactivity receiving botulinum toxin A (BOTOX®) therapy in Germany

Abstract: This is the first study demonstrating the clinical usefulness of Botox therapy in clinical practice. Successful treatment resulted in lower costs for NDO associated morbidity due to less need for incontinence aids and UTI medication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 21 publications
3
21
0
1
Order By: Relevance
“…However, although little is known regarding the pathology of low-compliance and break-low-compliance, data from this study suggest that BoNT-A treatment may beneWt these NBD as well. The frequency of micturition or clean intermittent catheterisation as well as the number of incontinence episodes was satisfactorily improved after BoNT-A (Botox ® ), conWrming previous Wndings [8,19,[24][25][26][27].…”
Section: Discussionsupporting
confidence: 55%
“…However, although little is known regarding the pathology of low-compliance and break-low-compliance, data from this study suggest that BoNT-A treatment may beneWt these NBD as well. The frequency of micturition or clean intermittent catheterisation as well as the number of incontinence episodes was satisfactorily improved after BoNT-A (Botox ® ), conWrming previous Wndings [8,19,[24][25][26][27].…”
Section: Discussionsupporting
confidence: 55%
“…Only 3 of 30 patients had symptomatic UTIs after injection, and they presented the least improvement in urodynamic parameters. Further retrospective studies with longer follow-up (1-6 years) confirmed the reduced incidence of UTIs, even after repeat BoNT/A injections [53•], resulting in decreased treatment costs [58]. Finally, a lack of association between BoNT/A and UTIs was concluded by the similar rate of UTIs between the placebo and the active drug population in the randomized controlled trial in NDO patients [17].…”
Section: Urinary Tract Infectionsmentioning
confidence: 83%
“…With the authors' model assuming a 6-month interval for repeated BoNT-A injections at the 200-U dose, the cost analysis revealed that BoNT-A was the least expensive of the three options. In 2010, Wefer et al [30] performed a European cost analysis as part of their report of 214 patients that also revealed a cost savings in incontinence aids and treatment of urinary tract infections.…”
Section: Cost Analysismentioning
confidence: 98%